Impulsive spike enhancement on gamelan audio using harmonic percussive separation - Solekhan Solekhan; Yoyon K. Suprapto; Wirawan Wirawan (Institute of Advanced Engineering and Science, 2019)
Impulsive spikes often occur in audio recording of gamelan where most existing methods reduce it. This research offers new method to enhance audio impulsive spike in gamelan music that is able to reduce, eliminate and even strengthen spikes. The process separates audio components into harmonics and percussive components. Percussion component is set to rise or lowered, and the results of the process combined with harmonic components again. This study proposes a new method that allows reducing, eliminating and even amplifying the spike. From the similarity test using the Cosine Distance method, it is seen that spike enhancement through Harmonic Percussive Source Separation (HPSS) has an average Cosine Distance value of 0.0004 or similar to its original, while Mean Square Error (MSE) has an average value of 0.0004 that is very small in average error and also very similar. From the Perceptual Evaluation of Audio Quality (PEAQ) testing with Harmonic Percussive Source Separation (HPSS), it has a better quality with an average Objective Difference Grade (ODG) of -0.24 or Imperceptible.